Pengembangan E-Modul Matematika Berbantuan Canva Untuk Meningkatkan Pemahaman Materi Pada Siswa Sma - Yunita Maulina; Supriyono Supriyono; Dita Yuzianah (International Forum of Researchers and Lecturers, 2023)
The aim of the research is to develop learning media in the form of electronic modules that are suitable for high school students to use. The development of this e-module product also aims to improve understanding of the material. This type of research is included in research and development. The research stages using the ADDIE model consist of: (1) needs analysis and material analysis stage, (2) design stage for making e-modules, (3) development stage by carrying out material validation and media validation, (4) implementation stage by carrying out tests extensive and limited testing, (5) evaluation stage. The research subjects for the limited test were 7 students of class XI IPS 2 and the broad test involved 36 students of class XI IPS 3. The data collection technique used was observation and using questionnaires and tests. The research data analysis technique goes through stages: (1) validity analysis, (2) practicality analysis, (3) effectiveness analysis, (4) gain test. The research results show that the e-module developed is suitable for use and can be said to be able to improve understanding of the material. Based on the research results, it shows that: (1) the average media expert score is 3.504 in the